Trans-contextual work: doing entrepreneurial contexts in the periphery - Muñoz, Pablo; Kimmitt, Jonathan; Spigel, Ben (Small business economics, 2024)
This study explores how entrepreneurs “do” contexts in peripheral areas. Through the examination of changes in roles, practices, and relationships across peripheral areas in Chile, we found that substantive transformations result from the momentary repurposing of systems of provision, types of inter-dependencies, and sources of reliance within public, community, and family contexts. Drawing from the perspective of interstitial spaces and extensive data, this is done through three interwoven interaction rituals: support seeking, neighboring, and nesting. We abductively theorize the connection between these rituals as trans-contextual work . As entrepreneurs do contexts through trans-contextual work new entrepreneurial ideas, practices and artifacts begin to reorganize community resources and transform the commune’s social into an entrepreneurial life. Our research expands the current understanding of contextual change in peripheral areas and contextualization in entrepreneurship more broadly. Plain English Summary How does a supportive context for entrepreneurship emerge in peripheral areas? While prior literature in this domain has focused on key drivers for supporting entrepreneurship there is typically a high growth and high innovation focus which may be less relevant when considering the diverse features of peripheral areas. Through detailed qualitative analysis, findings indicate how traditional community resources are re-purposed to support entrepreneurial activities. This transformation of communities is described as “trans-contextual work” involving support seeking, neighboring, and nesting which occurs in often informal and temporary settings (e.g., community football clubs) known as “interstitial spaces.” Consequently, we see that supportive environments for entrepreneurship emerge through this process, occurring across public, community, and family contexts. This has important theoretical implications for understanding how entrepreneurs enact their contexts. Practically, the findings imply that many peripheral areas are actually rich in supportive mechanisms for entrepreneurship, but that may not be observed through traditional lenses.